Penerapan Permainan Tradisional Congklak untuk Mengembangkan Kemampuan Konsep Berhitung Pemula dan Motorik Halus Anak Usia 4–5 Tahun di TK Hati Suci Jakarta [Application of the Traditional Congklak Game to Develop Beginner Numeracy Skills and Fine Motor Skills in Children Aged 4-5 Years at Hati Suci Kindergarten, Jakarta] - Rahmat, Tiara Juliana (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2022)
This research was conducted to develop the ability of beginner numeracy skills and fine motor skills of 4–5 year children by implementing the traditional Congklak game, which aims to describe the ability of beginner numeracy concepts and fine motor skills of children aged 4–5 years after the implementation of traditional Congklak game. The method used in this research is classroom action research which is carried out in three cycles with 2 actions in each cycle. The results obtained were the children's beginner's numeracy ability on indicator 1 increased in cycle III to 33.75%. In indicator 2, it increases in cycle III to 45.00%. In indicator 3, it increases in cycle III to 38.75%. And the percentage results on the assessment of children's fine motor skills on indicators increased in cycle III to 18.75%. In indicator 2 it increases to 38.75%. In indicator 3 it increases to 28.75%. It can be concluded that the application of traditional Congklak game can develop beginner numeracy skills and fine motor skills in children aged 4–5 years.